Conference proceedings as a matter of bibliometric studies: the Academy of International Business 2006-2008 - (:unkn) unknown (SPRINGER, 2010)
This study does a bibliometric analysis based on keywords of conference proceedings. Scientometric investigations of conference proceedings are a new and innovative, not very common approach. The studies and papers presented may be interpreted as early indicators of scientific development. The Academy of International Business (AIB) was chosen for being the leading organization for studies in international business with contributions covering a 3-year period (2006-2008). The study presents the general structure of current scholarly interest in international business studies, clusters the keywords and reflects details on the focused research areas of the papers analyzed. The bibliometric analysis indicates three clusters: the core, the semi-periphery and the periphery. The five most occurring keywords were found to be multinational enterprise, emerging markets, foreign direct investment, internationalization and knowledge management in descending order. The analyses focus on concepts building the core (in total ten keywords), the semi-periphery which is coined by performance and related topics (60 keywords) and the periphery of the studies with governance and specific facets of it (199 keywords).
Keywords: Conference proceedings; International business; Methodology; Scientometrics; Content analysis; Theory development; FOREIGN DIRECT-INVESTMENT; GLOBALIZATION; INFORMATION; COCITATION; RANKING; SCIENCE